INFLUENCE OF INTERNAL LABOR FACTORS ON WORK ACCIDENTS OF XX TOLL ROAD CONSTRUCTION PROJECT - Sitti Safiatus Riskijah (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
Abstract The XX Toll Road Construction Project is a national project with high risk and high complexity, given the nature of the work that requires clearing new land on hills and valley areas which requires retaining wall works. During its implementation, work accident occurence can be caused by many factors, including labor factors. This study aims to determine the effect of internal labor factors on work accidents occurred at XX Toll Road Construction Project. The data required in the form of primary data obtained from questionnaires about occupational safety and health, and fitness measurements using the Balke method. The data analysis used Multiple Regression analysis with SPSS. The results showed that the internal factors of the workforce, namely the factors of work safety, occupational health, and workforce fitness simultaneously have strong and significant effect on the occurrence of work accidents in the project. Hence, these internal factors partially bring significant effect. Keywords: labor, safety, health, fitness, accidents